2018
DOI: 10.1152/ajpcell.00082.2017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UT-A1- and AQP2-interacting proteins in rat inner medullary collecting duct

Abstract: The urea channel UT-A1 and the water channel aquaporin-2 (AQP2) mediate vasopressin-regulated transport in the renal inner medullary collecting duct (IMCD). To identify the proteins that interact with UT-A1 and AQP2 in native rat IMCD cells, we carried out chemical cross-linking followed by detergent solubilization, immunoprecipitation, and LC-MS/MS analysis of the immunoprecipitated material. The analyses revealed 133 UT-A1-interacting proteins and 139 AQP2-interacting proteins, each identified in multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Immunoprecipitated proteins were excised from SDS-PAGE gels and digested as previously described (Chou et al, 2018 ). Briefly, the excised gel pieces were washed twice in 50% acetonitrile (ACN) for 30 min and 100% ACN for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitated proteins were excised from SDS-PAGE gels and digested as previously described (Chou et al, 2018 ). Briefly, the excised gel pieces were washed twice in 50% acetonitrile (ACN) for 30 min and 100% ACN for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins that form complexes with AQP2 are likely to be phosphorylated by the same protein kinases as AQP2. Consequently, we asked what proteins identified as AQP2-binding proteins in a previous mass spectrometry-based study (15) have sites that showed increases in phosphorylation. These proteins are shown in Table 6, with the protein kinases that phosphorylate them.…”
Section: F796 Vasopressin Signaling In the Collecting Ductmentioning
confidence: 99%
“…The effect of vasopressin on protein-protein interactions in the collecting duct was also recently studied. By focusing on the UT-A1, a known urea transporter regulated by vasopressin, Chou et al (30) used chemical cross-linking, followed by immunoprecipitation of UT-A1 in native rat IMCD cells, incubated with or without dDAVP for 15 min to study its interacting partner proteins. LC-MS/MS analysis revealed 25 partner proteins significantly changed in its binding with UT-A1 in response to dDAVP.…”
Section: Iii) S264mentioning
confidence: 99%